Efektivitas Edukasi Cybersecurity dalam Meningkatkan Pengetahuan Siswa tentang Ancaman Digital pada Siswa Menengah Atas - Agung, Hamzah (Universitas Muhammadiyah Gorontalo, 2025)
The development of information and communication technology has brought new challenges for teenagers, particularly in facing digital threats such as phishing, misuse of personal data, and the dangers of artificial intelligence (AI). This study aims to examine the impact of cybersecurity education on improving the knowledge and awareness of students at SMA Muhammadiyah 9 Surabaya regarding digital literacy in the context of digitalization, social media, and AI. Using a quantitative approach with a quasi-experimental design (one-group pretest-posttest), the study involved 30 students from grades XI and XII as respondents. Data were collected through pretests and posttests, then analyzed using SPSS. The results indicate a significant increase in all measured aspects: internet knowledge (+4.5), data security (+8.33), phishing links (+10), and AI-related risks (+10.17). These findings suggest that cybersecurity education not only enhances technical understanding but also fosters a new awareness of digital risks previously unrecognized by students. Therefore, integrating cybersecurity topics into the school curriculum is highly recommended to develop a digitally literate, critical, and responsible generation.